Avaliação econômica do cultivo da soja em Rotação e sucessão de culturas: um estudo de Caso no município de Ourinhos-SP - Mello, Donizeti Aparecido [UNESP] (2015)
The production of soy (Glycine Max (L.) Merril) is an important crop for the county of Ourinhos – SP due to the size of the rural area that surrounds the county because small, medium and large properties mainly plant soy in this area. This study aimed to conduct an economic analysis which evolves two procedures of the production of soy: the rotation of crops and the succession of crops in three different crops (2010/11, 2011/12 e 2012/13). The methodology used for the development of this study was the case study, and it was the basis for raising costs of the production and the development of a model, which is used by Instituto de Economia Agrícola (IEA). Therefore the effective operating cost (COE), the total operating cost (COT) and the profitability were analysed. Two properties in the county of Ourinhos were analysed for the development of this study. The results from the three crops indicated that in the 2010/11 crop and in the 2011/12 crop the COE in the succession of crops were bigger than in the rotation crop in 3,4 %, and in the 2012/13 crop, the COE in the succession of crops were 3,2% bigger. If it is analysed the COT in the three crops, it was noticed that the production expenses were bigger than the cost related to the rotation of crops, showing a difference of 2,6% in the 2010/11 crop, 1,8% in the 2011/12 crop and 2,5% in the 2012/13 crop. While analysing the productive profitability between the two procedures, the rotation of crops proved to be bigger in all of the three crops, and in the 2010/11 crop the difference was 8 more bags per hectare; in the 2011/12 crop the difference was 18 more bags per hectare and in the 2012/13 crop the difference was 4 more bags per hectare. The profitability indicators were also better in the rotation of ...